Follow‐up and growing‐up formula promotion among Mexican pregnant women and mothers of children under 18 months old - Mireya Vilar‐Compte; Sonia Hernández Cordero; Ana C. Castañeda‐Márquez; Nigel Rollins; Gillian Kingston; Rafael Pérez‐Escamilla (Maternal and Child Nutrition, 2022)
Abstract Milk formula sales have grown globally, particularly through follow‐up formulas (FUF) and growing‐up milks (GUM). Marketing strategies and weak regulatory and institutional arrangements are important contributors to caregivers' decisions about child feeding choices. This study describes maternal awareness, beliefs, and normative referents of FUFs and GUMs among Mexican pregnant women and mothers of children 0–18 months (n = 1044) through the lens of the theory of reasoned action (TRA). A cross‐sectional survey was undertaken in two large metropolitan areas of Mexico. Descriptive analyses were conducted following the constructs of the TRA. One‐third of the participants had heard about FUFs, mainly through health professionals (51.1%) and family (22.2%). Once they had heard about FUFs, the majority (80%) believed older infants needed this product due to its benefits (hunger satisfaction, brain development, and allergy management). One quarter of the participants were already using or intended to use FUFs; the majority had received this recommendation from doctors (74.6%) and mothers/mothers‐in‐law (25%). Similarly, 19% of the women had heard about GUMs. The pattern for the rest of TRA constructs for GUMs was similar to FUFs. Mexican women are exposed to FUFs and GUMs, once women know about them, the majority believe older infant and young children need these products, stating perceived benefits that match the poorly substantiated marketing claims of breast‐milk substitutes. Health professionals, particularly doctors, act as marketing channels for FUFs and GUMs. Marketing of FUFs and GUMs represents a threat to breastfeeding in Mexico and a more protective regulatory and institutional environment is needed.